2019
DOI: 10.1177/2045125318820207
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the scientific literature on atypical antipsychotic drugs in the United Kingdom: a bibliometric study

Abstract: Objective:A bibliometric study was undertaken of peer-reviewed publications on atypical antipsychotic drugs (AADs) from the United Kingdom and the findings are presented herein.Methods:We selected the documents from the Scopus database. We applied several production and dispersion bibliometric indicators, including Price’s law on the growth of the scientific literature, and Bradford’s law. We also calculated a so-called ‘participation index’ across different countries. The bibliometric data were thereafter cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…High scores are positively correlated with domestic violence, as assessed by the EPDS (Bacchus et al, 2004 ). Studies have shown that pregnant women with an unstable personality are more prone to PPD, and according to the incidence of PPD, the personality of pregnant women can be sequentially ranked by type as: introverted–unstable, extroverted–unstable, extroverted–stable, and introverted–stable (López-Muñoz et al, 2019 ). Psychoanalysts believe that women become more primitive or childish in their behavior during pregnancy and after childbirth, and this change can cause psychological conflict.…”
Section: Discussionmentioning
confidence: 99%
“…High scores are positively correlated with domestic violence, as assessed by the EPDS (Bacchus et al, 2004 ). Studies have shown that pregnant women with an unstable personality are more prone to PPD, and according to the incidence of PPD, the personality of pregnant women can be sequentially ranked by type as: introverted–unstable, extroverted–unstable, extroverted–stable, and introverted–stable (López-Muñoz et al, 2019 ). Psychoanalysts believe that women become more primitive or childish in their behavior during pregnancy and after childbirth, and this change can cause psychological conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometrics and evaluation of research performance have been carried out on a wide range of health topics [7][8][9][10][11][12][13][14][15], and several have been carried out in the fields of environmental studies [16,17], and toxicology [18][19][20][21][22][23][24]. Yet, to the best of my knowledge, only a few bibliometric studies in food contamination have been done recently [25][26][27][28], and only one bibliometric study explicitly focused on aflatoxin has been published by using Web of Science (WoS) database for data collection [28].…”
Section: Introductionmentioning
confidence: 99%
“…After downloading the metadata and exact bibliographic details of all melatonin publications, the results were analyzed according to the criteria of chronological distribution, country of origin, affiliation, sources and authors of the documents, keywords and descriptors used. The methodology applied in this study was comparable to recent bibliometric studies of our group (32,34,37,38).…”
Section: Data Categorizationmentioning
confidence: 89%
“…Bibliometrics includes the collection, processing and management of quantitative bibliographic data from scientific publications (20), and their statistical indicators allow measurement of the growth, size and distribution of scientific literature on the topic in question during a given time period (21). Our research group has studied, using a bibliometric approach, the evolution of scientific literature in different areas of neurosciences by several research groups, involving diverse psychiatric disorders and characteristics related, as well as specific therapeutic tools in the field of psychopharmacology (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), including the evolution of publications on the pineal gland during the period 1966-1994 (35), and 1900-2014 (36). In this sense, to detail its distribution, and interpret the changes that have affected its development, we focused our attention on the bibliometric analysis of the scientific production on melatonin since the discovery of this hormone in 1958 until 2019, to identify the groupings and trends of the research on this topic.…”
Section: Introductionmentioning
confidence: 99%